Cross layer design of IEEE 802.11e enhanced distributed channel access wireless network for telemedicine application - Putra, Emansa Hasri (Institute of Electrical and Electronics Engineers, 2009)
Telemedicine system requires an acceptable network quality of service and cost. IEEE 802.11 wireless LAN technology has been developed to provide scalable and low cost network. For telemedicine application however, the technology does not fulfil the quality of service requirement yet. In order to overcome this problem, a cross layer design of wireless LAN is proposed. The design is based on IEEE 802.11e Enhanced Distributed Channel Access (EDCA) and IEEE 802.11g standards in datalink and physical layers. This has been implemented in NS2 simulation environment. The simulation has been performed to deliver four traffics flows with different priorities. Simulation result shows that the cross layer design has better throughput value when delivering the video data than the conventional IEEE 802.11b wireless LAN. Thus, the new design has a potential to be used in telemedicine system